(untitled) (Medico Legal Update, 2020)
Background: Quick breastfeeding during the third stage of labour is considered the safest and most effective intervention to reduce the blood loss associated with labour, as it can naturally release the oxytocin to stimulate the uterine contraction. These contractions make it easier to dislodge the placenta and help reduce the total duration of the third stage of labour. Aim of the Study: To evaluate the impacts of breastfeeding immediately after birth for the total duration of the third stage of labour. Study Design: A quasi-experimental study, post-test only control design. Material and Method: 300 pregnant women from the labour ward in their third stage of labour participated in this study, carried out between 26th of February 2020 and 30th of July 2020. Samples were selected by using a convenient sampling technique through the structured observation record sheet, onto which the beginning of breastfeeding time and placental delivery was recorded. The data were analyzed using descriptive and inferential statistics. Results: Among the 300 mothers (34%) had delivered the placenta within 5 minutes, (46%) within 8-10 minutes, (13.3%) within 11-13 minutes and (6.7%) had 14-16 minutes in the experimental groups. While, in the control group the duration was longer (46.7%) between 11 and 13 minutes, (20%) within 14 and 16 minutes. Conclusion: The study results show that early initiation of breastfeeding is an effective intervention to reduce the total duration of the third stage among the mothers during the third stage of labour.